2018
DOI: 10.1002/clc.22884
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the renin‐angiotensin‐aldosterone system in patients with arrhythmogenic right ventricular dysplasia: A double‐blind, multicenter, prospective, randomized, genotype‐driven study (BRAVE study)

Abstract: Arrhythmogenic right ventricular dysplasia (ARVD) is a rare cardiomyopathy characterized by the progressive replacement of cardiomyocytes by fatty and fibrous tissue in the right ventricle (RV). These infiltrations lead to cardiac electrical instability and ventricular arrhythmia. Current treatment for ARVD is empirical and essentially based on treatment of arrhythmia. Thus, there is no validated treatment that will prevent the deterioration of RV function in patients with ARVD. The aim of the BRAVE study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(12 reference statements)
2
7
0
Order By: Relevance
“…ACEI/ARB exhibit anti-remodeling effects in various types of cardiomyopathies ( 21 , 22 ). This study revealed that ACEI also showed such an effect in patients with ARVC, which is compatible with the findings of Morel et al ( 23 ), who showed that ACEI had an anti-fibrotic effect in patients with ARVC. Although the detailed pathogenesis of ARVC remains unclear, the major pathophysiological features include cardiomyocyte loss, fibrogenesis, and adipogenesis, which lead to the progression of ventricular dilation and dysfunction ( 24 26 ).…”
Section: Discussionsupporting
confidence: 93%
“…ACEI/ARB exhibit anti-remodeling effects in various types of cardiomyopathies ( 21 , 22 ). This study revealed that ACEI also showed such an effect in patients with ARVC, which is compatible with the findings of Morel et al ( 23 ), who showed that ACEI had an anti-fibrotic effect in patients with ARVC. Although the detailed pathogenesis of ARVC remains unclear, the major pathophysiological features include cardiomyocyte loss, fibrogenesis, and adipogenesis, which lead to the progression of ventricular dilation and dysfunction ( 24 26 ).…”
Section: Discussionsupporting
confidence: 93%
“…This observation led to the hypothesis that modification of the RAAS axis, and probably TGFβ signalling in parallel, could have a similar role in ACM-driven fibrosis. The BRAVE study 223 was designed to address the effects of the angiotensin-converting-enzyme inhibitor ramipril in ACM, with planned initiation in January 2019. Ramipril was specifically chosen because this drug has been reported to normalize PPARγ expression, and increased PPARγ activity been implicated in ACM pathogenesis 224,225 .…”
Section: Discussionmentioning
confidence: 99%
“…ACEI/ARB exhibit anti-remodeling effects in various types of cardiomyopathies (21,22). This study revealed that ACEI also showed such an effect in patients with ARVC, which is compatible with the findings of Morel et al (23), who showed that ACEI had an anti-fibrotic effect in patients with ARVC. Although the detailed pathogenesis of ARVC remains unclear, the major pathophysiological features include cardiomyocyte loss, fibrogenesis, and adipogenesis, which lead to the progression of ventricular dilation and dysfunction (24)(25)(26).…”
Section: Discussionsupporting
confidence: 91%